Implementation of the Simultaneous Elections of the 2021 Lebak Regency in the Midst of the Covid-19 Pandemic (Study of Cibuah Village, Warungunung District) - Ombi Romli; Agus Fanar Syukri; Riant Nugroho (Neolectura, 2022)
The simultaneous village head election of Cibuah Village, Warunggunung District, Lebak Regency, is carried out based on Regent Regulation Number 7 of 2015 concerning Procedures for Simultaneous Village Head Elections. This study aims to provide an overview of the implementation of the 2021 Simultaneous Village Head Election in Cibuah Village, Warunggunung District, Lebak Regency in the midst of the Covid-19 Pandemic. This research uses a qualitative approach by collecting data through observation, interviews, and document studies. The results of this study show that the implementation of the Pilkades in the midst of the Covid-19 Pandemic in Cibuah Village was successfully implemented in accordance with changes to Regent Regulation Number 7 of 2015 concerning Procedures for Simultaneous Village Head Elections. However, the pilkades was marked by violations of health protocols by the public, and the occurrence of money politics carried out by candidates for village heads. These violations occurred due to the absence of an independent institution that supervised the running of the Elections.